A Morphological Analysis Of Derivational Affix In Short StoryOf The Happy Prince - Actavine, Achira Putri, Drs. Sigit Haryanto, M.Hum, Dr. Dwi Haryanti, M.Hum (2014)
This research paper elaborates a morphological analysis of derivational affix in short story of the Happy Prince. The objectives of research are to describe the types of derivational affixes and the functions of those of derivational affixes in short story of the Happy Prince. The researcher employs the descriptive qualitative research as a type of the research. The data sources consist of short story of the Happy Prince. The method of collecting data is reading completely the short story of the Happy Prince, classifying the word or sentences in every short story and writing the derivation affix.The technique of analysis data is comparing method. The results of the study are as follows. First types of derivational affixes found in short story of The Happy Prince. Prefix data appear in different form of prefix, such as En-, Re-, and Em-. While in suffix data appear in certain form, such as -or + -s, -ful, -er+ -s, -ly, -able, -ship, -ment, -ing, -en, -ly + -est, -ish + - ly, and -er. The total data of prefixes in The Happy Prince short story are 3 data, they consist of Enlarge, Remarks, and Embalmed. The total data of suffixes in The Happy Prince short story are 197 data, they consist of Councilors, Wonderful, Courtiers, Listlessly, Sensible, Courtship, Attachment, Flirting, Golden, Loveliest, Weighing, Feverishly, Gently, and Tumbler.